Nutrient Profiling of Tropical Soybean (Glycine Max) Core Collection (Global Journal of Science Frontier Research, 2020)
Abstract not found
Keywords: food composition; total protein; total oil content; palmitic acid; stearic acid; oleic acid; linoleic acid